Bentuk Morfologi Leksikon yang Digunakan Dalam Tradisi Merariq Masyarakat Suku Sasak di Lombok - Baiq Yuliatin Ihsani; Hilmiyatun H (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The purpose of this study is to describe the morphological form of the lexicon used in the merariq tradition of the Sasak Tribe community in Lombok. The methods used in achieving these goals include 1) methods of determining research subjects, 2) data collection methods, and 3) data analysis methods. The method of determining research subjects using purposive sampling is to select informants according to the research objectives. The data collection methods used are observation methods, interview methods, and documentation methods. Data analysis is carried out by making data reduction by means of abstraction, which is taking data that is appropriate to the research context and ignoring data that is not needed. Based on the results of data analysis, it can be concluded that the morphological form of the lexicon used in the merariq tradition of the Sasak Tribe community in Lombok consists of basic words, finished words, and groups of words (phrases).